Optimasi produksi biosurfaktan dari bakteri Bacillus cereus menggunakan minyak jelantah - Mardiah, Irma; Hamdani, Syarif; Fatimah, Ika; Setiani, Nur Asni; Hamdani, Syarif; Astriany, Dewi (Jurnal Biologi Udayana, 2022)
Biosurfactant is a microorganisms metabolite product that have antibacterial activities. The purpose of this study was to obtain optimal conditions in the production of biosurfactants from Bacillus cereus by utilizing waste frying oil as a carbon source. In this study, variations in the optimized production conditions included the concentration of waste frying oil, labelled 2%, 3%, 4%, and 5% and the medium pH at 6, 7, and 8. The study was using Mineral Salt Medium as production medium, the amount of inoculum concentration was 10% v/v (10 8 CFU/ml), agitation speed 160 rpm and incubation at room temperature. The optimal conditions for biosurfactant production were determined based on the best emulsification index. The biosurfactant extraction was carried out using a combination of chloroform and methanol (2: 1) solvents. The best concentrations of waste frying oil was 3%, and the best medium pH was 6. Biosurfactants produced from Bacillus cereus bacteria was 8,9 g/L with an emulsification index value 57,17%.